Rapid M1 Hemoclips Arteriotomy Repair After Emergency Coil Embolectomy. Issue 1 (26th February 2018) - Saad, Hassan; Krisht, Khaled M; Yang, Wei-hsun; Aboud, Emad; Krisht, Ali F
Abstract: BACKGROUND: The vascular closure staple clips have been studied in animal models and shown to have comparable results with sutured repair when it comes to the healing process, degree of vessel narrowing, and risk of thrombosis. However, they are clearly superior when the speed of application is taken into account, and they were clinically used in many vascular repair processes. Nevertheless, their usefulness in intracranial vascular surgery has not been described. OBJECTIVE: To describe the usefulness of hemoclips in fast and efficient repair of medium-sized and large intracranial vessels. METHODS: Two female patients diagnosed with giant symptomatic cavernous sinus aneurysms were undergoing elective endovascular procedures that were complicated by the dislodgement of coils into the M1 segment of the middle cerebral artery. Both patients were treated performing M1 arteriotomies and coil embolectomy. To avoid prolonged temporary occlusion in the M1 perforator's territory, the arteriotomies were repaired using microhemoclips in less than 10 min with re-establishment of flow. RESULTS: In both patients, flow was re-established in the M1 segments. In 1 patient, the coils extended to the temporal M2 causing intimal injury and leading to diminished flow. M1 segments in both patients were patent on later angiographic studies. CONCLUSION: We describe the advantage of emergent cerebrovascular arteriotomy and embolectomy in a rapid repair process that helped avoid massive ischemic injury. We believe this technique should be added to the armamentarium of neurosurgical cerebrovascular options.